Bark anatomy of four species of Cinnamomum (Lauraceae) from Kerala - MANILAL, M SHYLAJA, K S (Journal of Spices and Aromatic Crops, 1992)
Bark anatomy of four species of Cinnamomum - three cultivated (C. verum, C. cassia, C. camphora) and the most common wild cinnamon (C. malabatrum) arereporLed here. They differ with regard to many characters such as the nature of the scierenchymatous groups in the pericyciic region, nature of the phloem rays, distl;bution of phloem fibres and in the presence of crystalline inclusions. The differences in the bark structure are useful in distinguishing the genuineness of the true cinnamon (C. verum) bark and also in the taxonomy of the genus.